A rice LRR receptor‐like protein associates with its adaptor kinase OsSOBIR1 to mediate plant immunity against viral infection. Issue 11 (3rd August 2021) - Zhang, Hehong; Chen, Changhai; Li, Lulu; Tan, Xiaoxiang; Wei, Zhongyan; Li, Yanjun; Li, Junmin; Yan, Fei; Chen, Jianping; Sun, Zongtao
Summary: Plants sense pathogen attacks using a variety of receptors at the cell surface. The LRR receptor‐like proteins (RLP) and receptor‐like kinases (RLK) are widely reported to participate in plant defence against bacterial and fungal pathogen invasion. However, the role of RLP and RLK in plant antiviral defence has rarely been reported. We employed a high‐throughput‐sequencing approach, transgenic rice plants and viral inoculation assays to investigate the role of OsRLP1 and OsSOBIR1 proteins in rice immunity against virus infection. The transcript of a rice LRR receptor‐like protein, OsRLP1, was markedly up‐regulated following infection by RBSDV, a devastating pathogen of rice and maize. Viral inoculation on various OsRLP1 mutants demonstrated that OsRLP1 modulates rice resistance against RBSDV infection. It was also shown that OsRLP1 is involved in the RBSDV‐induced defence response by positively regulating the activation of MAPKs and PTI‐related gene expression. OsRLP1 interacted with a receptor‐like kinase OsSOBIR1, which was shown to regulate the PTI response and rice antiviral defence. Our results offer a novel insight into how a virus‐induced receptor‐like protein and its adaptor kinase activate the PTI response and antiviral defence in rice.